Three-dimensional model of the optical effect for an augmented reality application - Grankina, V.; Kulishova, N. (ХНУРЭ, 2017)
This work concerns augmented reality technology. Augmented reality is a process of viewing the real world and the virtual objects at the same time, where virtual information is superimposed in the physical world. Three -dimensional models of optical effects should be reliable, but at the same time, provide application files with minimal volumes. To carry out these requirements, it is proposed to use three-dimensional primitives in combination with effects in the augmented reality environment and with specially prepared textures.
Keywords: optical effect; optical